기후변화에 따른 농업생산성 변화의 일반균형효과 분석 - 권오상; Oh Sang Kwon; 이한빈; Han Bin Lee (자원·환경경제연구, 2012)
본고는 농업부문 및 국가경제에 대한 기후변화의 장기적 영향을 분석한다. 우선 작물 시뮬레이션 및 준모수적 분석법 등을 이용하여 쌀, 낙농 및 축산업에 대한 기후변화의 생산성 영향을 예측하고, 다음으로 축차적 동태 CGE모형을 이용하여 예측된 생산성 영향으로 유발되는 경제적 영향을 평가한다. 분석결과 우선 기후변화의 생산성 영향에서, 낙농 및 축산업의 경우 지속적으로 생산성이 하락하는 것으로 예측되었고, 쌀의 경우, 작물 시뮬레이션 적용 시 생산성 하락이, 준모수적 분석법을 적용 시 생산성이 상승한 후 다시 하락하는 것으로 예측되었다. 다음으로 쌀의 두 가지 예측결과를 기준으로 두 가지 시나리오를 설정하고 축차적 동태CGE모형에 반영하여 경제적 영향을 평가한 결과, 2050년 연간 GDP 예상손실률이 시나리오에 따라 각각 0.2%, 0.02%로 나타났으며, 세부부문별로는 농업생산부문과 식품가공업, 농업용 투입재 산업, 그리고 몇몇 유통관련 산업에서 경제적 효과가 크게 나타났다. 그리고 대부분의 선행연구에서 간과되던 낙농 및 축산업 부문의 경제에 미치는 영향이 큰 것으로 나타났는데, 위결과는 쌀부문 외 다른 농업생산부문에서의 기후변화 효과분석이 필요함을 제시한다. This study analyzes the long-run impacts of climate change on Korean agriculture and economy. We estimate the impacts of climate change on the productivities of major agricultural products including rice, dairy and livestock using both a simulation approach and a semiparametric econometric model. The former predicts a decline in productivity while the latter predicts an increase in productivity due to climate change, especially for rice. A recursive dynamic CGE model is used to analyze the general equilibrium impacts of productivity change under the two different scenarios, derived from the two productivity analysis approaches. The loss of GDP in 2050 is 0.2% or 0.02% of total GDP depending on the scenario. It is shown that the losses in dairy and livestock sectors are larger than that in rice sector, although the losses in those two non-rice sectors have been ignored by most existing works.